Implementation of Tutoring in Increasing Learning Interest of Elementary School Students at SD Negeri 054870 Tanjung Jati Kec. Binjai, Langkat Regency - Novi Tari Simbolon; Eti Muliani; Riza Dwina Br Ginting; Nisa Oktaviana Br Bangun; Miya Amanda Sembiring (Indonesian Journal of Society Development, 2023)
Interest in learning and lack of motivation are the main problems faced by students at SD Negeri 054870 Tanjung Jati. It can be seen that children at this school have a lack of awareness of educational matters, therefore the importance of tutoring will motivate students to be aware of the importance of education for the future. So that the lecturers and students of Quality Berastagi University aim to hold tutoring activities to increase the learning interest of elementary school students at public elementary school 054870 tanjung jati. This service focuses on grade 4 students. The research method used is descriptive qualitative. Based on the results of the service implementation, this tutoring activity has a significant impact such as increasing understanding, growing awareness in learning, children are more active in discussing and asking about material that is not understood